2020
DOI: 10.1002/acn3.51186
|View full text |Cite
|
Sign up to set email alerts
|

Association of genetic variants in migraineurs with and without restless legs syndrome

Abstract: Objective: Several single-nucleotide polymorphisms (SNPs) are associated with restless legs syndrome (RLS). This study investigated whether or not additional SNP variants increase the risk of RLS in migraineurs and in migraine with aura (MA) and migraine without aura (MoA) subgroups. Methods: Migraineurs with and without RLS were genotyped using an Affymetrix array. We performed association analyses for the entire cohort and the MA and MoA subgroups, which were divided further into episodic migraine (EM) and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…We previously identified that a single-nucleotide polymorphism (SNP) rs2300478 at MEIS1, the gene responsible for iron homeostasis [ 23 ], increased the risk of RLS by 1.42-fold in migraine subjects via a candidate gene approach [ 24 ]. A recent small-scaled GWAS also suggested additional genes may contribute to RLS in migraineurs [ 25 ]. To further decipher the role of genetic variants in RLS in patients with migraine, we implemented a two-stage GWAS followed by in vivo functional analyses with zebrafish [ 26 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…We previously identified that a single-nucleotide polymorphism (SNP) rs2300478 at MEIS1, the gene responsible for iron homeostasis [ 23 ], increased the risk of RLS by 1.42-fold in migraine subjects via a candidate gene approach [ 24 ]. A recent small-scaled GWAS also suggested additional genes may contribute to RLS in migraineurs [ 25 ]. To further decipher the role of genetic variants in RLS in patients with migraine, we implemented a two-stage GWAS followed by in vivo functional analyses with zebrafish [ 26 28 ].…”
Section: Introductionmentioning
confidence: 99%